Impact of Hot Air Drying on the Physicochemical Indicators, Astaxanthin Stability, and Degradation Kinetics of Antarctic Krill - Tiantian MA; Zhefei XIAO; Jie OUYANG; Jian SHEN; Xiaolin HOU (Shipin gongye ke-ji)
To investigate the effects of hot air drying on the physicochemical indicators, astaxanthin stability, and degradation kinetics of Antarctic krill, the study analyzed the changes in physicochemical indicators of Antarctic krill under different drying conditions to reveal the impact of drying conditions and physicochemical indicators on astaxanthin stability, and to establish a degradation kinetics model for astaxanthin. The results showed that the physical and chemical indicators of Antarctic krill changed during the hot air drying process: the material temperature went through three stages: preheating, constant temperature, and heating; The moisture content decreased with increasing drying temperature and time. As the drying time increased, the L* value decreased, while the a* and b* values increased; As the drying temperature increased, the L*, a*, and b* values first increased and then decreased; The protein and fat content showed a trend of first increasing and then decreasing with the increase of drying temperature and time. Stability analysis of astaxanthin during hot air drying: astaxanthin retention rate decreased with increasing drying temperature and time; Astaxanthin retention rate was negatively correlated with drying time, material temperature, protein and fat contents and a* and b* values, and positively correlated with water content and L* values, in which water content, L* and a* values were the main direct influencing factors, and material temperature was the main indirect influencing factor. Dynamics analysis of astaxanthin degradation: The degradation rate constant k of astaxanthin increased with increasing drying temperature; The degradation of astaxanthin during the preheating stage followed first-order reaction kinetics, with an activation energy of 50.287 kJ/mol; The degradation of astaxanthin during the constant temperature and heating stages followed zero and first-order combined kinetics, with activation energies of 44.351 and 64.246 kJ/mol, respectively.